Evaluation of Financial Performance of BIST Participation Banks: CAMELS and Multi-Criteria Decision Making (MCDM) Approach - Bulut, Emre; Simsek, Ahmed Ihsan (My University, 2024)
This study presented an evaluation of the financial performances of six Turkish participation banks with feats of being registered in Borsa Istanbul for the year 2023. The analysis employed 20 different financial ratios using the CAMELS rating. The weighting method of this study was determined to be the CRITIC approach. The financial performances of the 6 participation banks traded in BIST were performed with the weighting method of the CAMELS rating and the CRITIC approach. The performance evaluation was done with the ARAS, TOPSIS, and COPRAS methodologies. As can be observed from the tables, it is clear that EMLAK Katılım Bank has the highest performance in all three methods. Making an evaluation, one can safely argue that the participation banks’ financial performance provides similar results in the three different ways. The similarity, plus the reliability, and the validity of these analyses conducted in this study are that the utilization of the TOPSIS, COPRAS, and ARAS approaches yield similar results.
Keywords: MCDM; CRITIC; CAMELS; Participation Banks; Financial Performance